Assessment of Five Electron‐Shuttling Molecules in the Extracellular Electron Transfer of Electromethanogenesis by using Methanosarcina barkeri. Issue 18 (15th September 2020) - Liang, Tian‐Tian; Zhou, Lei; Irfan, Muhammad; Bai, Yang; Liu, Xue‐Zhi; Zhang, Ji‐Liang; Wu, Zong‐Yang; Wang, Wen‐Zhuo; Liu, Jin‐Feng; Cheng, Lei; Yang, Shi‐Zhong; Ye, Ru‐Qiang; et al.
Abstract: Electron‐shuttling molecules (ESMs), natural or synthetic, are utilized by microorganisms as electron acceptors or donors to facilitate electron transfer. In this study, five ESMs, namely anthraquinone‐2‐carboxylic acid (AQC), 9, 10‐anthraquinone‐2‐sulfonicacid (AQS), 9, 10‐anthraquinone‐2, 6‐disulfonic acid (AQDS), Neutral red, and Thionin, were selected to assess their effects on electromethanogenesis under different electrochemical potentials and concentrations. Results showed that the rate of methanogenesis achieved in the presence of AQC was 7.4 times higher than that of the control (without ESMs) at −850 mV (vs. Ag/AgCl). The effectiveness on methanogenesis followed AQC, Neutral Red, AQS, AQDS, and Thionin in a decreasing order. Compared with the control, the addition of ESMs did not affect the biomass of methanogens significantly. Meanwhile, qPCR analysis of the ccdA gene indicated that the abundance of the Cytochrome  c gene and the extent of CO2 reduction to methane correlated positively. The promoting effect of the selective ESMs on methanogenesis was mainly related to their electron transfer capabilities. Abstract : Shuttle bus : Electron‐shuttling molecules (ESMs) are added into the cathode chamber of microbial electrosynthesis (MES) cells to accelerate the methane production rate. The electromethanogenesis is promoted by ESMs in the order: AQC>Neutral red>AQS>AQDS>Thionin. The fundamental mechanism is attributed to the ability of the organic ESM to transfer electrons. In addition, the expression level of the ccdA gene for Cytochrome  c is correlated to electromethanogenesis rate.